(−)-Epigallocatechin Gallate Targets Notch to Attenuate the Inflammatory Response in the Immediate Early Stage in Human Macrophages - Wang, Tengfei; Xiang, Zemin; Wang, Ya; Li, Xi; Fang, Chongye; Song, Shuang; Li, Chunlei; Yu, Haishuang; Wang, Han; Yan, Liang; Hao, Shumei; Wang, Xuanjun; et al. (Frontiers in Immunology, 2017)
Inflammation plays important roles at different stages of diabetes mellitus, tumorigenesis and cardiovascular diseases. (−)-Epigallocatechin gallate (EGCG) can attenuate inflammatory responses effectively. However, the immediate early mechanism of EGCG in inflammation remains unclear. Here, we showed that EGCG attenuated the inflammatory response in the immediate early stage of EGCG treatment by shutting off Notch signaling, and that the effect did not involve the 67-kD laminin receptor (67LR), the common receptor for EGCG. EGCG eliminated mature Notch from the cell membrane and the nuclear Notch intercellular domain (NICD), the active form of Notch, within 2 min by rapid degradation via the proteasome pathway. Transcription of the Notch target gene was downregulated simultaneously. Knockdown of Notch 1/2 expression by RNA interference impaired the downregulation of the inflammatory response elicited by EGCG. Further study showed that EGCG inhibited lipopolysaccharide-induced inflammation and turned off Notch signaling in human primary macrophages. Taken together, our results show that EGCG targets Notch to regulate the inflammatory response in the immediate early stage.